1983
DOI: 10.1111/j.1365-2125.1983.tb02228.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced increments in plasma levels of propranolol and noradrenaline.

Abstract: Exercise‐induced changes in the plasma levels of propranolol and noradrenaline were determined in nine volunteers. Total plasma propranolol levels were increased during submaximal treadmill exercise, with exercise‐induced increments of 13 +/‐ 4% at 4 h after the last dose, 18 +/‐ 7% at 9 h and 41 +/‐ 5% at 16 h. Exercise‐induced increments in plasma propranolol were observed after single as well as repeated doses. During exercise, increments in plasma propranolol were correlated temporally with changes in plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In addition to the different effects of beta-blockers obtained in the present study, it was shown recently that pharmacokinetic properties of third generation beta-blockers also differ significantly from those of first and second generation beta-blockers: It was shown previously that plasma concentrations of propranolol, atenolol and bisoprolol markedly increase during exercise [25,26,27,28,29]. The reason for this increase might be the fact that propranolol and atenolol are taken up into, stored in and released from adrenergic cells during exercise together with epinephrine and norepinephrine, thus causing an increase of plasma concentrations of these drugs together with those of epinephrine and norepinephrine during exercise [30,31,32,33,34,35].…”
Section: Discussionmentioning
confidence: 93%
“…In addition to the different effects of beta-blockers obtained in the present study, it was shown recently that pharmacokinetic properties of third generation beta-blockers also differ significantly from those of first and second generation beta-blockers: It was shown previously that plasma concentrations of propranolol, atenolol and bisoprolol markedly increase during exercise [25,26,27,28,29]. The reason for this increase might be the fact that propranolol and atenolol are taken up into, stored in and released from adrenergic cells during exercise together with epinephrine and norepinephrine, thus causing an increase of plasma concentrations of these drugs together with those of epinephrine and norepinephrine during exercise [30,31,32,33,34,35].…”
Section: Discussionmentioning
confidence: 93%
“…Nerve-stimulation induced release of propranolol was also observed in the spleen and the vasculature of the perfused canine hindlimb (Russell et al, 1983). Similarly, in man, treadmill exercise was found to produce a simultaneous elevation of propranolol and NA in the plasma of hypertensive patients and normal volunteers receiving therapeutic doses of drug (Hurwitz et al, 1983). Thus, propranolol release in association with sympathetic nerve stimulation appears to represent a generalized phenomenon at adrenergic neuroeffector junctions and, conceivably, may contribute to pharmacological actions of the drug at vascular and other synapses.…”
Section: Introductionmentioning
confidence: 90%
“…Mean plasma oxprenolol concentrations 24 h after dosing were 100-250 ng ml-', and in all subjects terminal plasma concentrations exceeded 50 ng ml-', levels at which adequate P-adrenoceptor blockade can be maintained (Theeuwes et al, 1985). Transient exercise induced increases in plasma levels of lipophilic ,-adrenoceptor antagonists have been reported in animals (Powis & Snow, 1978) and in normal human subjects (Hurwitz et al, 1983). These changes may reflect redistribution of 3-adrenoceptor antagonists at site(s) of action (evidence cited by Hurwitz et al, 1983).…”
Section: Discussionmentioning
confidence: 67%
“…Transient exercise induced increases in plasma levels of lipophilic ,-adrenoceptor antagonists have been reported in animals (Powis & Snow, 1978) and in normal human subjects (Hurwitz et al, 1983). These changes may reflect redistribution of 3-adrenoceptor antagonists at site(s) of action (evidence cited by Hurwitz et al, 1983). The increases in plasma oxprenolol concentrations (mean 2.5%) were smaller than those reported for propranolol (13-14%) by Hurwitz et al (1983), although these may represent only a fraction of the changes at receptor sites.…”
Section: Discussionmentioning
confidence: 87%